OPTIMASI PRODUKSI JAMUR KUPING (STUDI KASUS DI SANGGAR TANI MEDIA AGRO MERAPI DI DUSUN GROGOL DESA UMBULHARJO KECAMATAN CANGKRINGAN KABUPATEN SLEMAN YOGYAKARTA) - Budiarto Budiarto; Heni Handri Utami; Dwi Kukuh Arifanto (Jurnal Dinamika Sosial Ekonomi, 2010)
This research aims lo analysze optimum production and to know the profit of Mushroom (A uricularia polytrica) (wet mushroom and dry mushroom) Sanggar Tani Media Agro Merapi in the Grogol village Umbulharjo, Cangkringan, Sleman, Yogyakarta. This research using descriptive method and it’s implementation using survey method. The data using primary data and secondary data. Data analysis optimum production of Mushroom (Auricularia polytrica) using linear programming and a analize the applied independent sample t-test. Result of the research indicated that optimum production of Mushroom (Auricularia polytrica) Sanggar Tani Media Agro Merapi is wet mushroom 5000kgs and dry Mushroom is required by 7143 Kgs, consisted of wet Mushroom and 1,428,6 Mushroom Kgs. With sale to both types of the Mushroom (Auricularia polytrica) optimal value of maximum acceptance receiving equal fo Rp 80. 000. 000. Based on the the test result with independent sample t-test can conclude that there are profit differences pf sale between wet Mushroom types and Mushroom. The dry Mushroom profit is higher than wet Mushroom.Keywords: Optimum production of Mushroom (Auricularia polytrica), profit.